Sexual dimorphism among medical students of north India assessed by interorbital circumference index - Vishal Kalia; Rohit Kumar Sharma; Kunal Chawla; Garima Sharma; Praveen Sharma (Asian Journal of Medical Sciences, 2023)
Background: The human body dimensions are affected by ecological, geographical, racial, gender, and age factors. Craniofacial anthropometry has become an important tool used in genetic counseling, reconstructive surgery, and forensic medicine. Orbital measurements are important in the evaluation of several systemic syndrome, craniofacial abnormalities, and also surgical treatment of post-traumatic telecanthus. Among these measurements, normal interpupillary distance, inner canthal distance (ICD), and outer intercanthal distance are the vital features to be known. Aims and Objectives: The aims and objectives of the present study were to assess the ICD, head circumference (HC), and circumference orbital index of male and female medical students of North India and find out gender differences in the respective parameters and thus to contribute the present finding to the available literature. Materials and Methods: This was an observational descriptive study conducted in the department of anatomy at a fixed time in 150 MBBS course students in the age group 18–22 years. The ICD and HC were measured using round end digital spreading Vernier caliper. Then, circumference interorbital index (CII) was calculated and analyzed. Results: The mean ICD in males was 3.44±0.33 mm and in females was 3.21±0.32 mm; mean HC in males was 56.03±1.55 mm and in females was 53.88±1.38 mm; and mean CII in males was 6.15±0.54 and in females was 5.95±0.51. Conclusion: The result of this study will help to establish the mean values for of craniofacial anthropometric parameters for medical students of North India, and the results are showing that craniofacial anthropometric parameters are sexually dimorphic.